Evaluation of Adhesive Joints Between Coating and Substrate Using Ultrasonic Spectroscopy - Marian Josko; Marcin Jarmuzek (Communications - Scientific letters of the University of Zilina, 2001)
In the paper the theoretical analysis of ultrasonic impulse signal and experimental investigations on some specimens was carried out. The specimens were made of constructional steel on which some coatings of automotive putty and lacquer were layered. In particular, the sensitivity of selected parameters of ultrasonic spectrum on changes of condition of the substrate and bonded materials was studied. It was noticed that irregularities of substrate and the thickness of coatings layered, influence parameters of the ultrasonic signal spectrum.